Transformation of Ilahiya and Qasida During the National Revival of Bosniaks: From the Expression of Piety to the Bosniak National Song - Krupalija, Mustafa (Journal of History Culture and Art Research, 2022)
Although very complicated, the relationship between religion and music is often the subject of very close complementarity. Such a close encounter is noticeable in the life of religious Sufis in Bosnia and Herzegovina, who for centuries used the ilahiya and qasida as an expression and reflection of their piety. In this paper, we will try to define the socio-political context in which the ilahiya and qasida, as an expression of piety, experienced a transformation into a song of national character. This period was the 1990s when ilahiyas and qasidas served Bosniaks not only as an important differentiating religious basis but also as an important element in the national revival and the construction of their national identity. As a basis for our claims, we will analyze the repertoire of ilahiyas and qasidas from before the 1990s, as well as ilahiyas and qasidas which were composed and published during the 1990s. As such, they have also gotten the role of war songs, combat songs of vigorous emotional intensity, with a Bosniak as the central theme, who is presented as a devout believer and a sincere Muslim.